PENGARUH CAHAYA BIRU TERHADAP PENYERAPAN NITROGEN DAN FOSFOR DALAM LIMBAH CAIR PETERNAKAN SAPI SERTA KANDUNGAN KARBOHIDRAT Chlorella zofingiensis DÃ¶nz. DALAM FOTOBIOREAKTOR DATAR - , AMININ; , Eko Agus Suyono, S. Si., M. App. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chlorella zofingiensis is an unicellular photosynthetic organism that can use nitrogen and phosphorous as nutrition for its growth and carbohydrate production. Microalgae growth can be improved using blue light treatment. Liquid livestock waste contains high nitrogen and phosphorous concentration can be used for improving the microalgae growth. The increase of growth it followed by carbohydrate production benefits for ethanol production. The microalgae was cultivated in flat photobioreactor using Â¼ Bold Basal Medium (BBM) supplemented by liquid livestock waste with sunlight as a control and a blue light treatment for increasing biomass production. The parameters were cell numbers